Reproductive Phenology of the patauá palm (Oenocarpus bataua Mart.) cultivated under the conditions of Belém-PA (Research, Society and Development, 2021)
This paper aimed to evaluate the reproductive phenology of patauá palm cultivated in Belém, Pará, Brazil. Monthly monitoring carried out on 163 plants in the full reproductive phase of the Active Germplasm Bank of Embrapa Amazônia Oriental for 55 months based on three flowering and four fruiting events and their interactions with six meteorological variables. The occurrence rate and the synchrony of each event calculated, in addition to the simple correlation and the principal components analysis between the events and the meteorological variables. Flowering and fruiting events occurred every month, with rates ranging from 0.6% (dry inflorescence) to 58% (bract emission). The most frequent phenophases were the emission of bracts, inflorescences in flowering and bunches with immature fruits. Five events were asynchronous, and two had little synchrony, such as the phenophases of emission of bracts and bunch with immature fruits. The peak of flowering occurred from October to December and the fruiting from November to February. Most of the events were few influenced by the climatological variables. It can considered that, in the conditions of the study, the patauá palm presents reproductive phenological events in all months, being asynchronous and with overlapping flowering and fruiting peaks.